Dynamic buckling analysis of reinforced composite plate subjected to harmonic loads - Dat, Pham Tien; Binh, Le Pham (Vietnam Journal of Mechanics, 2023)
Composite plates are high-tech structures used in many areas of modern engineering, like building, space travel, ships, etc. In practice, these structures are often used in their thin form, typically a reinforced composite plate subjected to dynamic loads. Therefore, when subjected to loads, the plate may be instability. The article presents the element model, finite element algorithm, and buckling analysis results of reinforced composite plates subjected to dynamic loads in order to determine the buckling domain. Furthermore, the influence of some factors such as geometric parameters, reinforcing stiffeners, and material characteristics on the buckling domain of the plate is studied in detail.